2019
DOI: 10.30604/jika.v4i2.188
|View full text |Cite
|
Sign up to set email alerts
|

Family characteristics as risk factors of stunting among children age 12-59 month

Abstract: A B S T R A C TStunting in children (low height for age) increases morbidity and mortality rate. It can lead to poor intelligence and productivity, and degenerative diseases. The objective of this research was to investigate the associations of family characteristi stunting in children aged 12-59 months who visited the integrated health posts in Ratu Samban District, Bengkulu City. The hypothesis of this research was there were associations of family characteristics with stunting in children aged 12 months who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(24 reference statements)
1
0
0
1
Order By: Relevance
“…There is no relationship between the number of family members and the incidence of stunting. This is in line with previous research which stated that the number of family members was not related to the incidence of stunting (Khairani, 2019). Fulfillment of family intake needs is influenced by family income, if the family income is middle and above the intake needs (Shahar et al, 2019) Another study revealed that there was a relationship between the number of family members and the incidence of stunting, it was found that almost half of the stunted children had more than four family members.…”
Section: Discussionsupporting
confidence: 88%
“…There is no relationship between the number of family members and the incidence of stunting. This is in line with previous research which stated that the number of family members was not related to the incidence of stunting (Khairani, 2019). Fulfillment of family intake needs is influenced by family income, if the family income is middle and above the intake needs (Shahar et al, 2019) Another study revealed that there was a relationship between the number of family members and the incidence of stunting, it was found that almost half of the stunted children had more than four family members.…”
Section: Discussionsupporting
confidence: 88%
“…Demikian pula dengan situasi bayi dan balita, nutrisi yang diperoleh sejak bayi lahir sangat berpengaruh terhadap pertumbuhannya termasuk risiko terjadinya stunting (Kementerian Kesehatan RI, 2018b). Determinan utama terjadinya stunting pada anak di Indonesia menurut kerangka konsep WHO adalah ASI tidak eksklusif, penyakit infeksi, status ekonomi keluarga yang rendah, kelahiran prematur, panjang badan baru lahir yang pendek, usia ibu, ibu yang pendek, status gizi ibu, tingkat pendidikan orangtua rendah, berat badan dan panjang badan lahir, anak yang tinggal di daerah miskin perkotaan dan di daerah pedesaan (Beal et al, 2018) (Doddy, 2019 (Henuk et al, 2021) (Khairani & Effendi, 2019) (Wemakor et al, 2018).…”
Section: Pendahuluanunclassified